A Feasibility Analysis on CHAI tea making facility and tea salon - Bantola, Timothy E.; Lucero, Pinky; Vargas, Vina. (Diliman, Quezon City College of Engineering, 2004)
The following conclusions can be made from the Social Profitability Study: The venture under study, Chai Tea, has numerous beneficial effects to society, the government, and to the Filipino citizen. Some primary social benefits include the stimulation of local and foreign industries, the generation of tax funds, and the creation of jobs; while among secondary social benefits are support for institutions such as employment agencies, SSS, and Pag-Ibig; the generation of the need for public utility vehicles; and additional revenues due to the use of utilities such as electricity and drinking water. Externalities also arose from the establishment of the company. Some possible technological externalities include possible generation of small business near the factory and the reduction of health-related problems in the country; while pecuniary externalities include an increase in factor rates of hire. The various social costs and benefits were quantified and cost-benefit analysis was applied. Three socio-economic criteria were used: net present value method; internal rate of return; and the benefit-cost ratio. At a social discount rate of 12%, all three criteria showed the project as socially acceptable. These conclusions show that the project is Socially Profitable.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Chai; Tea; Tea trade; Participatory monitoring and evaluation (Project management)